Progreso y desafíos en la era cuántica. - Almudéver, Carmen G. (Pasajes: Revista de Pensamiento Contemporáneo, 2025)
The article focuses on the progress and current challenges of quantum computing, a technology based on principles of quantum mechanics such as superposition, entanglement, and interference, which promises to revolutionize multiple scientific and industrial sectors. It describes how quantum computers, which use quantum bits or qubits, have the potential to solve complex problems in areas such as molecular simulation, logistical optimization, and cryptography, highlighting the threat they pose to current encryption systems like RSA. The main technologies for building quantum processors are presented, including superconducting circuits, trapped ions, and neutral atoms, and the importance of improving the quality and quantity of qubits, as well as error correction, is emphasized in order to achieve large-scale, fault-tolerant quantum computers. Finally, it is noted that quantum computing will not replace classical computing but will complement it, opening a new era in information processing with a potential impact comparable to that of electricity or the internet.